7th International scientific conference on defensive technologies OTEH-2016 (proceedings review) - Pokorni, Slavko J. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The article presents the basic information about the overal results, the significance, the international programme committee and the working areas of the 7th International Scientific Conference on Defensive Technologies, OTEH 2016, in comparison with the previous six conferences. The number of sections, number of papers, number of authors/coauthors, number od sessions and number of members of the scientific commitees are presented in the review. This year conference has had the smalest number of papers but the biggest number of authors/coauthors since this conference was held for the first time.